Impact of dairy farms on groundwater quality in a productive basin in the northeast of the Pampean Plain, Argentina - Cellone, Francisco; Santucci, Lucia; Borzi, Guido; Tanjal, Carolina Verónica; Di Lello, Claudia; Butler, Lisandro; Cordoba, Joaquín Alejandro; Lamarche, Luciano; Galliari, María Julieta; Melendi, Emilia; Delgado, M.I.; Carol, Eleonora (Elsevier, 2023)
The Pampean Plain is a relevant world food production area where livestock and agricultural activities are developed. The northeast of this region is characterized by dairy production, where large quantities of excreta from the animals to the substrate cause environmental impacts associated with soil and groundwater contamination. On these dairy farms, the same water sources are used for animal nutrition, cleaning of facilities, and home consumption by rural workers. Groundwater quality assessment is therefore crucial to guaranteeing safe production and human supply. The aim of this work is to analyse the impact of family dairy farming on the geochemical processes that govern the groundwater quality of aquifers used for domestic and animal consumption in productive basins of the northeast Pampean Plain. An analysis of major ions, nitrates, and phosphates in groundwater was performed in 42 wells sampled at different periods. Also, sediments in diverse sectors were collected to be analysed for available phosphorus. The main point sources of contamination that were identified derive from farm facilities’ cleaning and the degradation of animal excrement. These sources infiltrate toward the unsaturated zone and reach the groundwater, or they directly enter through poorly constructed perforations. This produces reactions in the unsaturated zone, releasing protons and generating the dissolution of carbonates, increasing the groundwater hardness. The chemical compounds registered may produce limitations in water quality for human consumption and the development of agricultural activities, affecting animal nutrition and the production of a dairy basin in the northeast of the Pampean Plain.